Collateral Arteriogenesis Involves a Sympathetic Denervation That Is Associated With Abnormal α-Adrenergic Signaling and a Transient Loss of Vascular Tone - Silva, Alexander; Hatch, Christopher J.; Chu, Megan T.; Cardinal, Trevor R. (Frontiers in Cardiovascular Medicine, 2022)
Stimulating collateral arteriogenesis is an attractive therapeutic target for peripheral artery disease (PAD). However, the potency of arteriogenesis-stimulation in animal models has not been matched with efficacy in clinical trials. This may be because the presence of enlarged collaterals is not sufficient to relieve symptoms of PAD, suggesting that collateral function is also important. Specifically, collaterals are the primary site of vascular resistance following arterial occlusion, and impaired collateral vasodilation could impact downstream tissue perfusion and limb function. Therefore, we evaluated the effects of arteriogenesis on collateral vascular reactivity. Following femoral artery ligation in the mouse hindlimb, collateral functional vasodilation was impaired at day 7 (17 ± 3% vs 60 ± 8%) but restored by day 28. This impairment was due to a high resting diameter (73 ± 4µm at rest vs 84 ± 3µm dilated), which does not appear to be a beneficial effect of arteriogenesis because increasing tissue metabolic demand through voluntary exercise decreased resting diameter and restored vascular reactivity at day 7. The high diameter in sedentary animals was not due to sustained NO-dependent vasodilation or defective myogenic constriction, as there were no differences between the enlarged and native collaterals in response to eNOS inhibition with L-NAME or L-type calcium channel inhibition with nifedipine, respectively. Surprisingly, in the context of reduced vascular tone, vasoconstriction in response to the α-adrenergic agonist norepinephrine was enhanced in the enlarged collateral (-62 ± 2% vs -37 ± 2%) while vasodilation in response to the α-adrenergic antagonist prazosin was reduced (16 ± 4% vs 73 ±6 %), indicating a lack of α-adrenergic receptor activation by endogenous norepinephrine and suggesting a denervation of the neuroeffector junction. Staining for tyrosine hydroxylase demonstrated sympathetic denervation, with neurons occupying less area and located further from the enlarged collateral at day 7. Inversely, MMP2 production was greater and closer to the enlarged collateral at day 7, suggesting that denervation may be related to extracellular matrix degradation during arteriogenesis. Further investigation on vascular wall maturation and the functionality of enlarged collaterals holds promise for identifying novel therapeutic targets to enhance arteriogenesis in patients with PAD.